2004
DOI: 10.1088/0268-1242/19/4/160
|View full text |Cite
|
Sign up to set email alerts
|

Photocreated carrier dynamics in isolated carbon nanotubes

Abstract: We report the first combined photoluminescence and pump-probe measurements on single wall carbon nanotubes isolated in micelles. The bandgap photoluminescence is observed at room temperature and is concomittent with a drastic change in the photocreated carrier dynamics as compared to the one observed in usual macroscopic samples. Probing the fundamental bandgap leads to a non-exponential dynamics which is related to a lifetime distribution within the macroscopic nanotube population. Probing the second van Hove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Raman, absorption, and photoluminescence ͑PL͒ spectroscopies have provided extensive characterization of specific SWNT species of both semiconducting and metallic electronic structure. [6][7][8] Recent time-resolved studies of SWNT charge carrier dynamics [9][10][11][12][13][14][15][16][17][18] have focused primarily on the transient response of semiconducting SWNTs. Many questions remain regarding the nature and dynamics of charge carrier relaxation, recombination, separation, and transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman, absorption, and photoluminescence ͑PL͒ spectroscopies have provided extensive characterization of specific SWNT species of both semiconducting and metallic electronic structure. [6][7][8] Recent time-resolved studies of SWNT charge carrier dynamics [9][10][11][12][13][14][15][16][17][18] have focused primarily on the transient response of semiconducting SWNTs. Many questions remain regarding the nature and dynamics of charge carrier relaxation, recombination, separation, and transport.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In contrast, optical studies of SWNTs dispersed as sodium dodecyl sulfate-͑SDS-͒encased micelles in water show clear interband transition features in the absorption spectrum, and corresponding band-gap photoluminescence. 6 Wavelength-degenerate pump-probe studies in the band-gap region of isolated SWNTs have been reported; 12,14 in addition to a fast initial Շ1 ps absorption bleach decay, these studies report a slower-decay component of as long as 30 ps which they attributed to interband carrier recombination in isolated SWNTs. The two-color pumpprobe work of Huang et al reports transient bleach signals of more than 100 ps lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…We have thus performed similar pump-probe measurements with a degenerate configuration in resonance with the first and second transitions of the semiconducting nanotubes for isolated nanotubes. 19 The data is systematically compared to the one obtained for deposited nanotubes. The signal obtained in resonance with the line S2 is shown on the inset of Fig.…”
Section: Isolated Nanotubesmentioning
confidence: 99%
“…12,21,22 On the other hand, in s-SWNT, intraband carrier relaxation and interband carrier recombination lead to fast and slow relaxations respectively. 12,[18][19][20] Environmental effects and defects also play a major role in these relaxation processes. 12,23 Chen et al 24 measured the Im͑ ͑3͒ ͒ ϳ 10 −10 esu whereas Maeda et al 10 reported that Im͑ ͑3͒ ͒ could be as high as 10 −6 esu in the case of s-SWNT films on a substrate.…”
mentioning
confidence: 99%
“…5,6,7 One dimensional nature of delocalized π-electron cloud along the tube axis, 8,9 make CNTs the most promising material with large and ultrafast electronic third order susceptibility 10 to be utilized in exciting applications like optical terahertz (THz) switching and passive modelocking. Femtosecond time resolved photoinduced studies on single walled nanotubes (SWNT) 11,12,13,14,15,16,17,18,19 reveal that the excitons are the primary photoexcitations in semiconducting-SWNT (s-SWNT) whereas free carriers are photoexcited in metallic-SWNT (m-SWNT). These studies indicate that the photoinduced response changes from fast (≤5 ps) to slow (30 ps) when the SWNTs are dispersed in a liquid from their bundled state.…”
mentioning
confidence: 99%